2014
DOI: 10.1371/journal.pone.0097098
|View full text |Cite
|
Sign up to set email alerts
|

MiR-422a as a Potential Cellular MicroRNA Biomarker for Postmenopausal Osteoporosis

Abstract: BackgroundMicroRNAs (miRNAs) are a class of short non-coding RNA molecules that regulate gene expression by targeting mRNAs. Recently, miRNAs have been shown to play important roles in the etiology of various diseases. However, little is known about their roles in the development of osteoporosis. Circulating monocytes are osteoclast precursors that also produce various factors important for osteoclastogenesis. Previously, we have identified a potential biomarker miR-133a in circulating monocytes for postmenopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
81
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(83 citation statements)
references
References 39 publications
(44 reference statements)
1
81
0
Order By: Relevance
“…The aforestated study was one of its first kinds in identifying miR-133a as a biomarker in circulating monocytes. The same group identified another miRNA in circulating monocytes, miR-422a, as a potential biomarker for postmenopausal osteoporosis [13]. More recently, 5 dysregulated miRNAs in osteosarcoma were identified in microarray analysis and upon further subjection to pathway analysis only miR-194-5p was enriched in osteoporosis related pathways suggesting miR-194-5p as a potential biomarker for postmenopausal osteoporosis [11].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The aforestated study was one of its first kinds in identifying miR-133a as a biomarker in circulating monocytes. The same group identified another miRNA in circulating monocytes, miR-422a, as a potential biomarker for postmenopausal osteoporosis [13]. More recently, 5 dysregulated miRNAs in osteosarcoma were identified in microarray analysis and upon further subjection to pathway analysis only miR-194-5p was enriched in osteoporosis related pathways suggesting miR-194-5p as a potential biomarker for postmenopausal osteoporosis [11].…”
Section: Discussionmentioning
confidence: 98%
“…A most recent study identified a range of dysregulated miRNAs in osteoporosis related pathways and suggests miR-194-5p as a viable biomarker for postmenopausal osteoporosis [11]. Similarly, miR133a and miR422a have been identified as potential biomarkers for postmenopausal osteoporosis [12,13]. The present study aims to expand the repertoire of dysregulated miRNAs in postmenopausal osteoporosis and identify other potential miRNA biomarkers for early detection of postmenopausal osteoporosis.…”
Section: Introductionmentioning
confidence: 93%
“…A number of investigators have used in vitro culture systems and animal models trying to elucidate the role of some miRNAs in the regulation of bone cell activity [6,10,[21][22][23][24][25][26][27][28][29]. However, only scarce data are available about the involvement of miRNAs in common human skeletal disorders, such as osteoporosis and osteoarthritis.…”
Section: Discussionmentioning
confidence: 99%
“…This group also demonstrated an apparent negative correlation between each of these 5 genes and miR-422a, although none of the correlations reached statistical significance. 80 These studies suggest that miR-422a is possibly involved in the regulation of postmenopausal osteoporosis and might be a potential biomarker of osteoporosis.…”
Section: Mir-422amentioning
confidence: 96%